Quantifying the role of chaperones in protein translocation by computational modeling - Assenza, Salvatore; De Los Rios, Paolo; Barducci, Alessandro (Frontiers in Molecular Biosciences, 2015)
The molecular chaperone Hsp70 plays a central role in the import of cytoplasmic proteins into organelles, driving their translocation by binding them from the organellar interior. Starting from the experimentally-determined structure of the E. coli Hsp70, we computed, by means of molecular simulations, the effective free-energy profile for substrate translocation upon chaperone binding. We then used the resulting free energy to quantitatively characterize the kinetics of the import process, whose comparison with unassisted translocation highlights the essential role played by Hsp70 in importing cytoplasmic proteins.